ANALISIS PENGANGGURAN TERBUKA DI PROVINSI RIAU - , Taryono, Tito Sanjaya Bakara ,Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims: (1) To analyze job opportunities in Riau Province; and (2) open unemployment in Riau Province in 2017-2021. The method used in this research is descriptive method. The data collection technique used is documentation. The results of this study indicate (1) Employment opportunities in Riau Province are dominated by the agricultural, forestry and fisheries sectors. (2) Open unemployment in Riau Province when viewed from the level of education completed is dominated by high school graduates. Open unemployment in Riau Province is dominated by men. Keywords:  Job Opportunities,   open unemployment